The Influence Of Different Binding Material On The Quality Of Rendang Boleces Fish Cob - Annisa Munawarah; Rahmi Holinesti (Jurnal Pendidikan Tata Boga dan Teknologi, 2021)
The background of this research is to find an alternative beef subtitutes in the manufacture of rendang by using cob fish, in addition to the price of cheap cob fish, cob fish is also easy to find in the market. The focus of this research is to know the effect of binding materials on the quality of rendang boleces of cob fish in terms of shape, colors, aromas, texture, and taste. This type of research is purely experimental, to reveal the effects and differences between the two variables. The research design used is the Completed Randomized Design. Researchers used primary data obtained from five expert panelists by filling out a research questionnaire. In testing the hypothesis, the researcher used the t test statistic, with a significant level of 5% (= 0.05). The result showed that there was no significant influence on the use of tapioca flour as binding agent with glutinous rice flour as binding agent on the quality of the shape, colors, aromas, texture, and taste of boleces of fish cob. From the statement, it is concluded that Ho was accepted due to the t count < t table.